REHABILITATION PROGRAM PHASE I POST RECONSTRUCTION ACL: A CASE STUDY - Nabila, N; Widodo, Agus; Wijaya, Dimas Zena (Academic Physiotherapy Conference Proceeding, 2021)
Introduction : Anterior Cruciate Ligament (ACL) injuries are the most common knee injuries during sports. The incidence of ACL rupture ranged between 30-78 people per 100,000 people per year. Most athletes with ACL injuries undergo reconstructive surgery in hopes of returning to do some sports activities. To accelerate and optimize conditions for a return to sport, a proper rehabilitation program is needed so that the patients can return to do some sports activities. According to protocol, proper rehabilitation involves exercises to increase muscle strength, knee ROM, proprioception, accompanied by reducing pain, and inflammation. Case Presentations : An 18 years old male patient came to physiotherapy with a diagnosis of post-ACL reconstruction. He did surgery a week before seeing the physiotherapy. The patient came with complaints of swelling and pain in the knee area. The pain increases when he bending the knee and doing activities that require support on the knee.. Management and Outcomes : Patients did 8-time therapies in 4 weeks. In one of the therapy sessions, the patient was given a rehabilitation program in the form of ice compression, ROM exercise, and isometric exercise. All of these rehabilitation programs will be evaluated with several measurement instruments, including; Pain measurement with NRS, anthropometric measurement with metline, measurement of muscle strength with MMT, and measurement of functional ability using KOOS. Discussion : The ACL post-reconstruction rehabilitation program is divided into 4 phases. Time for 0-6 weeks after surgery is included in phase 1 or what is known as an acute condition. The purpose of the program in phase 1 is to focus on reducing the risk of postoperative complications by reducing inflammation symptoms, maintaining joint mobility, and stimulating muscle contraction. The patient is given ice compression to reduce pain and reduce edema. Furthermore, ROM exercises are given to maintain joint mobility and flexibility of the tissues around the joints. The patient is also given isometric exercise to activate the muscles around the knee to improve knee joint stabilization. Conclusion: By providing interventions in the form of ice compression, ROM exercise, and isometric exercise, the post ACL reconstruction rehabilitation program in phase 1 can reduce pain, reduce edema, increase muscle strength and improve the patient's functional ability.